Factors Associated with Healthcare Effectiveness Data and Information Set (Hedis) Alcohol and Other Drug Measure Performance in 2014–2015. Issue 3 (July 2019) - Weisner, Constance; Campbell, Cynthia I.; Altschuler, Andrea; Yarborough, Bobbi Jo H.; Lapham, Gwen T.; Binswanger, Ingrid A.; Hechter, Rulin C.; Ahmedani, Brian K.; Haller, Irina V.; Sterling, Stacy A.; McCarty, Dennis; Satre, Derek D.; et al.
Background: Only 10% of patients with alcohol and other drug (AOD) disorders receive treatment. The AOD Initiation and Engagement in Treatment (AOD-IET) measure was added to the national Healthcare Effectiveness Data and Information Set (HEDIS) to improve access to care. This study identifies factors related to improving AOD-IET rates. Methods: We include data from 7 health systems with differing geographic, patient demographic, and organizational characteristics; all used a common Virtual Data Warehouse containing electronic health records and insurance claims data. Multilevel logistic regression models examined AOD-IET among adults (18+). Results: A total of 86, 565 patients had an AOD diagnosis qualifying for the HEDIS denominator. The overall initiation rate was 27.9% with wide variation; the overall engagement rate was 11.5% and varied from 4.5% to 17.9%. Women versus men (odds ratio [OR] = 0.81, 95% confidence interval [CI] = 0.76–0.86); Hispanics (OR = 0.85, 95% CI = 0.79–0.91), black/African Americans (OR = 0.82, 95% CI = 0.75–0.90), and Asian Americans (OR = 0.83, 95% CI = 0.72–0.95) versus whites; and patients aged 65+ versus 18–29 (OR = 0.82, 95% CI = 0.74–0.90) had lower odds of initiation. Patients aged 30–49 versus 18–29 (OR = 1.11, 95% CI = 1.04–1.19) and those with prior psychiatric (OR = 1.26, 95% CI = 1.18–1.35) and medical conditions (OR = 1.18, 95% CI = 1.10–1.26) had higher odds of initiation. Identification in primary care versus other departments was related to lower odds of initiation (emergency department [ED]: OR = 1.55, 95% CI = 1.45–1.66; psychiatry/AOD treatment: OR = 3.58, 95% CI = 3.33–3.84; other outpatient: OR = 1.19, 95% CI = 1.06–1.32). Patients aged 30–49 versus 18–29 had higher odds of engagement (OR = 1.26, 95% CI = 1.10–1.43). Patients aged 65+ versus 18–29 (OR = 0.51, 95% CI = 0.43–0.62) and black/African Americans versus whites (OR = 0.64, 95% CI = 0.53–0.77) had lower odds. Those initiating treatment in psychiatry/AOD treatment versus primary care (OR = 7.02, 95% CI = 5.93–8.31) had higher odds of engagement; those in inpatient (OR = 0.40, 95% CI = 0.32–0.50) or other outpatient (OR = 0.73, 95% CI = 0.59–0.91) settings had lower odds. Discussion: Rates of initiation and engagement varied but were low. Findings identified age, race/ethnicity, co-occurring conditions, and department of identification as key factors associated with AOD-IET. Focusing on these could help programs develop interventions that facilitate AOD-IET for those less likely to receive care.